Multispecies family: state-of-the-art and future directions in the Ibero-American context - Bedoya Díaz, Hugo Alejandro (Revista Colombiana de Ciencias Sociales, 2025)
Although, in recent years, the concept of a multispecies family has been the subject of intense scrutiny by professionals in different fields, to date no documentary reviews that offer a structured view of their research have been published. Therefore, this review aimed to identify peer-reviewed articles on multispecies families to determine the state of the art and its future directions. A documentary review was carried out using five databases to select the articles published in Spanish until 2023. Thematic analysis of forty-six investigations yielded four emerging dimensions that reflected the areas of discussion with the greatest growth in recent years: (a) legal recognition; (b) family dynamics; (c) physical and mental wellbeing; and (d) human-animal bond. Findings suggest that the integration of the “companion animal” into the family system improved the wellbeing of its members. The importance of creating institutional tools that identify human-animal violence as domestic violence in these families is discussed.